2007
DOI: 10.1103/physreve.76.046402
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of converging laser-created plasmas in semicylindrical cavities studied using soft x-ray laser interferometry

Abstract: PACS number(s): 52.50. Jm, 42.55.Vc AbstractThe evolution of dense aluminum and carbon plasmas produced by laser irradiation of 500 µm diameter semi-cylindrical targets was studied using soft x-ray laser interferometry. Plasmas created heating the cavity walls with 120 picosecond duration optical laser pulses of ~1×10 12 W cm -2 peak intensity were observed to expand and converge on axis to form a localized high density plasma region. Electron density maps were measured using a 46.9 nm wavelength tabletop capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…(2 ). Under these assumptions, the fringes will always bend in one direction when a plasma is probed, but from the anomalous results observed in many interferometer experiments [10][11][12][13][14][15] over the last four years it is clear that the traditional…”
Section: Analysis Of Interferometer Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2 ). Under these assumptions, the fringes will always bend in one direction when a plasma is probed, but from the anomalous results observed in many interferometer experiments [10][11][12][13][14][15] over the last four years it is clear that the traditional…”
Section: Analysis Of Interferometer Experimentsmentioning
confidence: 99%
“…Over the last four years interferometer experiments [10][11][12][13][14][15] of Al, Sn, Ag, and C plasmas have observed fringe lines bend in the opposite direction than was expected, indicating that the index of refraction was greater than one in parts of the plasma. Analysis of these experiments showed that the anomalous dispersion from the resonance lines and absorption edges of the bound electrons have a larger contribution to the index of refraction with the opposite sign as the free electrons [10][11][12][13][14][16][17][18] and their influence on the index of refraction extends far from the absorption edges and resonance lines.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast spectroscopic investigations of colliding laser plasma plumes have concentrated on short wavelength studies i.e. vacuum ultraviolet (VUV) 15 , extreme ultraviolet (EUV) and xray spectral ranges [16][17][18][19][20][21][22][23][24][25][26] . Attempts have also been made to simulate colliding laser plasma plumes for comparison with experimental results 21,[26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…This is based on collisional excitation pumping through a fast heating of the plasma. Such a soft X-ray laser has several applications in different areas of science and technology [16][17][18][19][20][21][22]. In fact, there exists a strong interest in extending the lasing wavelength toward shorter side.…”
mentioning
confidence: 99%